Multiletramentos na EJA: uma proposta de ampliação da competência leitora com a obra Quarto de despejo: diário de uma favelada de Carolina Maria de Jesus - Oliveira, Shirley Ornelas (2023)
This work is the result of a research that culminated in the elaboration of a didactic proposal based on the work Quarto de Despejo: Diário de uma favelada by Carolina Maria de Jesus. It was developed for a group of students from the final grades of the Youth and Adult Education, called Stage V, which corresponds to the 8th and 9th years of the State School of Alagoinhas, in the city of Alagoinhas, Bahia. Entitled: Multiliteracies in EJA: a proposal to expand reading proficiency with the work Quarto de Despejo: Diário de uma favelada by Carolina Maria de Jesus, aims to bring strategies to promote the increase of the students' reading proficiency in the mentioned class. Therefore, we assigned the following specific objectives: to analyze how a reading didactic proposal, supported by multiliteracy practices, can contribute to the expansion of the students' reading proficiency in EJA; to analyze the contributions that the chosen literary work can bring to the construction of meaning and thus assist in the process of expanding the students' reading proficiency; and to promote discussions about the identification and representation between the read and the lived, materialized in a literary text, from the analysis of the thematics present. The methodology adopted for the development of this work was the qualitative approach, based on the assumptions of pedagogical intervention research. Thus, the structure of this didactic proposal is based on Dolz and Schnewly (2004) and associated with the strategy proposed by Cosson (2021) for literary literacy, the expanded sequence, based on six stages: motivation, introduction, reading and interpretation, intervals, expansion and contextualization. As a strategy for the final production, we chose the creation of a reading diary to record our reading of the work, seeking to motivate students to externalize their reflections and critical analysis of what was read. Finally, this expanded didactic sequence takes into account the social contexts and discursive genres brought by the public concerning EJA, outlining paths for teaching and learning in a way that reading and writing are inserted in the diverse social practices of language and texts in circulation, in their most varied supports.